Tidal Swamps Development in West Kalimantan: Farmers Prefer A Rational-Moderately Strategy - Jajat Sudrajat; Sutarman Gafur (Faculty of Geography, Universitas Gadjah Mada, 2020)
The Indonesian government has spent lots of budgets and built more infrastructures to escalate the intensive rice farming in the tidal swamps since 1970s. However, the success story is very limited. This study aims to describe some obstacles in the practice of rice intensification, and also to explain some factors leading to their failure. In explaining this context, we refer them to our-own-experiences in tidal lowlands development project from 2008 to 2009, literatures study, and then it is deepened by doing collectives case study –that is consisting of three studies in the type of-B, C, and D overflows. The local farmers used to reject the intensive rice farming practices. The use of local paddy varieties is a prefer strategy option. It is closely related to minimize the farming cost and also as a strategy so that they have more time to manage another farm activities. Rationally the farmers prefer growing a variety of perrenial crop species that suits their personal needs and strategies. In conclusion, this study showed that agro-ecological based farm could be the most adaptive way in optimizing the indigenous rice farming.